Tinnitus Activities Treatment with Total and Partial Masking - Tyler, Richard S.; Stocking, Christina; Ji, Haihong; Witt, Shelley; Mancini, Patricia C. (Journal of the American Academy of Audiology, 2021)
Background There are many counseling and sound therapy approaches to treat tinnitus. Counseling approaches range from providing information using directive or collaborative approaches. Sound therapies include strategies that use background sounds to totally or partially mask tinnitus to reduce the prominence of or decrease the loudness or annoyance of the tinnitus.Purpose We evaluated the effectiveness of tinnitus activities treatment (TAT) in two groups, those without hearing aids (HA) and those who were provided with HA. In both groups, comparisons were made among those receiving (1) counseling only, (2) counseling and partial masking, and (3) counseling and total masking.Research Design Participants were provided with HA or not, based on their choice, and then randomly assigned to one of the three groups. The Tinnitus Handicap Questionnaire (THQ) was used as the primary measure.Results For those without HA, significant benefits were obtained for 8 out of 22 participants in the counseling group, 8 of 13 in the total masking group, and 8 of 24 in the partial mask group. The average decrease in the THQ was 15% for the counseling group, 25% for the total mask, and 14% for the partial masking group. For those with HA; significant benefits were obtained for 5 of 16 in the counseling group, 3 of 14 in the total mask group, and 6 of 13 in the partial mask group. The average decrease in the THQ score was 12% for counseling, 13% for total masking, and 16% for partial masking. No significant differences among groups were observed.Conclusion Individual differences were large. Many benefited from their treatment, but some did not. We believe this was likely influenced by their expectations.
Keywords: tinnitus; hearing loss; hearing aids; questionnaires